2004
DOI: 10.1007/s00213-004-1877-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sensitivity to reward in CB1 knockout mice

Abstract: These results demonstrate a modulatory role of CB1 in the determination of the rewarding properties of sucrose and probably, as suggested by previous studies, other reinforcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(91 citation statements)
references
References 37 publications
6
81
0
4
Order By: Relevance
“…During the maintenance phase of Experiment 1, CB1 KO mice responded significantly less for Ensure s under an FR1 schedule of reinforcement. The effect of CB1 KO on Ensure s -maintained responding was robust and persistent, observed for active nose-poke hole responding and food entries, and complements other reports that CB1 KO mice responded significantly less than WT controls for sucrose under an FR1 schedule (Sanchis-Segura et al, 2004) and for sucrose and Ensure s under PR schedules of reinforcement (Sanchis-Segura et al, 2004;Ward and Dykstra, 2005). Conversely, this is the first report in the literature on the effect of CB1 KO on responding for a fat reinforcer under a fixed-ratio schedule.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…During the maintenance phase of Experiment 1, CB1 KO mice responded significantly less for Ensure s under an FR1 schedule of reinforcement. The effect of CB1 KO on Ensure s -maintained responding was robust and persistent, observed for active nose-poke hole responding and food entries, and complements other reports that CB1 KO mice responded significantly less than WT controls for sucrose under an FR1 schedule (Sanchis-Segura et al, 2004) and for sucrose and Ensure s under PR schedules of reinforcement (Sanchis-Segura et al, 2004;Ward and Dykstra, 2005). Conversely, this is the first report in the literature on the effect of CB1 KO on responding for a fat reinforcer under a fixed-ratio schedule.…”
Section: Discussionsupporting
confidence: 85%
“…Other data from CB1 KO mice support the hypothesis that the CB1 receptor system can modulate intake of sweet palatable foods. It has been demonstrated, for example, that sucrose intake (Poncelet et al, 2003) and sucrose self-administration (Sanchis-Segura et al, 2004) are reduced in CB1 KO mice. Our laboratory recently reported that motivation for Ensure s is attenuated in CB1 KO mice, whereas motivation to consume corn oil is not attenuated in these mice (Ward and Dykstra, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…19 Given the high comorbidity between anxiety and major depression, 20 recent research has also focused on a potential role of the endocannabinoid system in the pathology of major depression 13,21 particularly of the melancholic subtype. 13 CB1 receptor-deficient mice share several symptoms with patients suffering from melancholic depression such as, for example, altered responsiveness to reward stimuli, 22 altered neurovegetative functions, 23 a predominance and persistence of aversive memories, 8,9 and possibly neurodegeneration. 24 Furthermore, it was shown by us and others that impaired endocannabinoid signaling can lead to sustained hyperreactivity of the hypothalamic-pituitaryadrenocortical (HPA) axis 23,25 and might also interfere with the proliferation of neural progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…CB 1 receptor activation increases extracellular dopamine overflow in terminal regions of the reward circuit, an effect reversed by CB 1 receptor blockade (Cheer et al, 2004;Tanda et al, 1997). In addition, genetic deletion of the CB 1 receptor results in a reduction in the sensitivity to the rewarding effects of sucrose (Sanchis-Segura et al, 2004). CB 1 receptor activation accentuates whereas CB 1 receptor blockade attenuates the rewarding effects of sweet and palatable foods (Ward and Dykstra, 2005).…”
Section: Introductionmentioning
confidence: 99%